Resistant Hypertension and Obstructive Sleep Apnea in the Setting of Kidney Disease - ABDEL-KADER, Khaled (2012)
OBJECTIVES: To explore the relationship between obstructive sleep apnea (OSA) and resistant hypertension in chronic kidney disease (CKD) and end-stage renal disease (ESRD). METHODS: We examined sleep parameters and blood pressure (BP) in 224 community-based, non-CKD participants from the Sleep-SCORE study, 88 non-dialysis dependent CKD and 95 ESRD participants. Unattended home polysomnography with standardized scoring protocols and automated BP monitors were used. Resistant hypertension was defined as a BP ≥ 140/90 mmHg despite ≥ 3 antihypertensives. RESULTS: Mean systolic BP of the CKD and ESRD groups were significantly higher than the non-CKD group (148.2mmHg [23.8], 144.5mmHg [26.7] vs. 132.2mmHg [26.7], respectively; P<0.0001) despite the use of more anti-hypertensive medications. The CKD and ESRD groups had higher rates of resistant hypertension than the non-CKD group (41.4%, 22.6% vs. 6.7%, respectively; P<0.0001). The severity of sleep apnea was associated with a higher risk of resistant hypertension. While resistant hypertension was associated with severe sleep apnea in participants with ESRD (odds ratio [OR] 7.1, 95% confidence interval [CI] 2.2-23.2), there was no significant association in the non-CKD (OR 3.5, 95% CI 0.8-15.4) or CKD groups (OR 1.2, 95% CI 0.4-3.7) after accounting for case-mix. CONCLUSION: The association between resistant hypertension and sleep apnea appeared robust in ESRD. OSA may contribute to resistant hypertension or both may be linked to a common underlying process such as volume excess. Future studies in patients with kidney disease should further characterize the resistant hypertension - OSA relationship and determine whether treatment of underlying mechanisms may improve outcomes.